Pengaruh Pengelolaan Dana Desa Dan Transparansi Penggunaan Dana Desa Terhadap Kesejahteraan Masyarakat Desa Nglorog Pada Masa Pandemi Covid-19 - Latifah Fitriyani; Nuwun Priyono (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
This research aims to prove the influence between village fund management and transparency and community welfare. This type of quantitative research, the preparation of hypotheses is based on agency theory which reflects the relationship between the government or agent and the community or principal. The sample used was the Nglorog Village community of 30 people who were determined using random purposive sampling. The research results found that village fund management and transparency had a significant positive effect on community welfare. And both variables have a simultaneous effect on the dependent variable. It is hoped that the research carried out can become a reference for the Nglorog Village government to improve its budget transparency system and make the human resources available to the Village Government more effective so that Village Fund Management is more targeted